(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2015)
La Troncal County is found in a strategic place of coast-highland eco-regional integration; being a vulnerable point in terms of its environmental care and its population’s health care. The population of La Troncal despite of its asymmetric economic growth; suffers from flaws in its sustainable development including its health care systems and good practices of environmental care. The flaws detected in Primary Health Care (PHC) and Primary Environmental Care (PEC), show which it should generate empowerment that allows a turn in health care from the obsolete medication model to one based on prevention – promotion and PHC together with PEC, that achieves wellness of the community facing a more humane a holistic future.